The impact of brominated flame retardants exposure on serum total bilirubin: A cross-sectional analysis - Shanshan Huang; Tong Lin; Jialu Chen; Fen Zhou; Junjie Yang; Haiyan Mao; Zhouxin Yang (PLoS ONE, 2025)
Background Brominated flame retardants (BFRs) are harmful, bioaccumulative, and persistent environmental pollutants, posing significant health risks. Elevated bilirubin levels can cause neurotoxicity and damage to the heart, liver, kidneys, and other organs. This study utilizes National Health and Nutrition Examination Survey (NHANES) data to investigate the association between exposure to BFRs and total bilirubin (TB) levels in adult participants. Methods Based on data from the NHANES 2007-2016, TB levels were divided into tertiles. Spearman’s rank correlation was used to analyze the relationship between individual BFRs and TB levels. Weighted linear regression analysis, restricted cubic splines (RCS), and stratified analysis were conducted to assess the correlation between individual BFRs and TB levels. Weighted quantile sum (WQS) regression and quantile-based g-computation (QGC) analysis were used to comprehensively evaluate the impact of BFRs exposure on serum TB levels. Results The study included 5831 participants. The results showed that PBB153, PBDE17, PBDE47, PBDE85, PBDE99, PBDE100, PBDE209, and PBDE183 were significantly correlated with TB levels (p <  0.05), with PBDE183 having the highest Spearman rank correlation coefficient of 0.292. After adjusting for confounding factors, most BFR remained significantly positively correlated with TB, while PBDE153 (β: - 0.031, 95%CI: - 0.317, 0.255, p =  0.829) and PBDE66 (β: 0.285, 95%CI: - 0.208, 0.777, p =  0.253) were not statistically significant. RCS analysis indicated that PBDE153 concentration had a significant U-shaped correlation with TB (p <  0.05), while PBDE17, PBDE99, PBDE154, and PBDE209 had an inverted “J”-shaped correlation (p <  0.05). PBB153, PBDE66, PBDE85, and PBDE183 also exhibited significant nonlinear S-shaped correlations with TB (p <  0.05). After stratification by age and gender, most individual BFR remained significantly positively correlated with TB levels (p <  0.05). WQS regression and QGC analysis indicated that mixed BFRs exposure was positively correlated with TB levels (β: 0.553, 95%CI: 0.384, 0.722, p <  0.001 and β: 1.060, 95%CI: 0.587, 1.532, p <  0.001), with PBDE183 contributing the most. Conclusions BFRs exposure is significantly positively correlated with TB levels, further suggesting the potential health impact of BFRs exposure on humans.